2011
DOI: 10.1149/1.3596545
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Ag Nanoparticulate Films Induced by Movable Rapid Thermal Annealing Applicable to Roll-to-Roll Processing

Abstract: A post-treatment process for metallic nanoparticle-based films using a movable halogen lamp is proposed to improve the microstructural density and the electrical conductivity. An annealing system that conceptually simplifies roll-to-roll processing was constructed, and the halogen lamp used as a heating source was designed to move instead of the substrate. When the liquid inkjetprinted film was annealed at a high heating rate, high density and near-bulk resistivity (2.64 X cm) were obtained. The microstructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Following UV sintering for over 10 minutes the traces remain largely resistive (>100 µΩ cm). Exposing the silver nanoparticle ink to the UV light for longer times further increases the temperature, analogous to Kim et al., [ 63 ] indicating that ink does not self‐limit the temperature of the traces. This suggests that there is a clear distinction between the mechanism leading the formation of a conductive silver film for the molecular ink presented here and that of silver nanoparticles.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Following UV sintering for over 10 minutes the traces remain largely resistive (>100 µΩ cm). Exposing the silver nanoparticle ink to the UV light for longer times further increases the temperature, analogous to Kim et al., [ 63 ] indicating that ink does not self‐limit the temperature of the traces. This suggests that there is a clear distinction between the mechanism leading the formation of a conductive silver film for the molecular ink presented here and that of silver nanoparticles.…”
Section: Resultssupporting
confidence: 55%
“…It has previously been reported that UV sintering of inkjet printed silver nanoparticles on silicon substrates yields highly conductive traces only when traces reach temperatures higher than 200 °C. [ 63 ] We carried out an analogous experiment with screen printed silver nanoparticle inks on PET and determined that exposure of traces to UV light produces an initially rapid temperature increase followed by a continuous rise in temperature throughout the sintering process (Figure S3, Supporting Information). Following UV sintering for over 10 minutes the traces remain largely resistive (>100 µΩ cm).…”
Section: Resultsmentioning
confidence: 99%
“…190 Since about 30% of the electrical power is converted into radiation, which is an order of magnitude higher than that of a typical laser, IPL sintering is a much more energy efficient technology. 146,193 Thus, the thermal equilibrium within the system was reached and the choice of substrate materials was restricted to those stable at high temperatures. 192 Localized heat dissipation only in the ink deposits is a necessary prerequisite for selective heating and sintering, but an equally important aspect is the time scale at which the irradiation is applied.…”
Section: Intense Pulsed Light (Ipl) Sinteringmentioning
confidence: 99%
“…The large surface area to volume ratio leads to many unique properties such as decreasing melting temperature (Tm). Nano-silver is currently the predominant type of ink used for printed electronics [8]- [12], with recent reports on the development of nano-copper ink. A conductive ink using copper nanoparticles is receiving more attention recently because copper is cheaper than gold or silver.…”
Section: Introductionmentioning
confidence: 99%